Norwegian Business Cycles 1982-2003 - Tore Anders Husebø; Bjørn-Roger Wilhelmsen (Norges Bank, 2005)
This paper analyses stylised facts regarding business cycles in Norway. We examine the empirical relationships between the aggregate business cycle and the cyclical components of individual macroeconomic time series. The results indicate that the stylised facts about Norwegian business cycles are fairly similar to the stylised facts about the US and the euro area cycles. Consumption and investment are strongly procyclical and broadly contemporaneous with the business cycle. Imports are procyclical and lead the cycle. Hours worked, the number of people employed and the unemployment rate are strongly correlated with the cycle and lag output by around 2 quarters. Domestic inflation is strongly procyclical and lags output by around 5 quarters. Consumption and real wage income are strongly and broadly contemporaneously correlated. Our results differ from the consensus opinion in the literature in that Norwegian labour productivity is acyclical and real wages are procyclical. While the latter deviation seems to be an inherent feature of the Norwegian economy, we argue that the cyclical behaviour of productivity in our sample has been significantly obscured by special factors in the 1990s.
hdl:11250/2508134
Keywords: 330